Features of world models of tax burden (Journal of Economic Research & Business Administration, 2016)
The paper considers four main models of tax burden which are now used on world practice: Anglo-Saxon, continental, Latin American and mixed. Each model is used by the different countries of the world on the geographical and economic features. In 2015 the average level of tax burden has shown 33-34% worldwide. Features of direct and indirect taxes of each model are analyzed. Proceeding from these indicators, each country forms their tax system. It is important to note that there is no ideal tax system, and it is possible to talk only about how this or that of them approaches satisfaction of the requirements facing it. Owing to different problems, the approaches to the organization of fiscal policy operating in the different countries not only very differ among themselves, but also rather conditionally realize the principles underlain in them.
Keywords: tax burden; tax system; models of tax burden; direct taxes; indirect taxes.